Osteogenic differentiation of mesenchymal stem cells is enhanced in a 45S5-supplemented β-TCP composite scaffold: an in-vitro comparison of Vitoss and Vitoss BA - Westhauser, Fabian; Karadjian, Maria; Essers, Christopher; Senger, Anne-Sophie; Hagmann, Sébastien; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (PLOS ONE, 2019)
Since the amount of autologous bone for the treatment of bone defects is limited and harvesting might cause complications, synthetic bone substitutes such as the popular β-tricalcium phosphate (β-TCP) based Vitoss have been developed as an alternative grafting material. β-TCPs exhibit osteoconductive properties, however material-initiated stimulation of osteogenic differentiation is limited. These limitations might be overcome by addition of 45S5 bioactive glass (BG) particles. This study aims to analyze the influence of BG particles in Vitoss BA (20 wt% BG particles with a size of 90-150 μm) on osteogenic properties, cell vitality and cell proliferation in direct comparison to Vitoss by evaluation of the underlying cellular mechanisms. For that purpose, Vitoss and Vitoss BA scaffolds were seeded with human mesenchymal stem cells (MSC) and underwent osteogenic differentiation in-vitro for up to 42 days. Cell vitality, proliferation, and osteogenic differentiation were monitored by quantitative gene expression analysis, determination of alkaline phosphatase activity, PrestoBlue cell viability assay, dsDNA quantification, and a fluorescence-microscopy-based live/dead-assay. It was demonstrated that BG particles decrease cell proliferation but do not have a negative impact on cell vitality. Especially the early stages of osteogenic differentiation were significantly improved in the presence of BG particles, resulting in earlier maturation of the MSC towards osteoblasts. Since most of the stimulatory effects induced by BG particles took place initially, particles exhibiting another surface-area-to-volume ratio should be considered in order to provide long-lasting stimulation.
Gesehen am 08.04.2019